Was Junia Really an Apostle? A Re-examination of Rom 16.7 - Burer, Michael H. (New Testament studies, 2001)
The identification of Junia in Rom 16.7 has been a familiar problem in biblical interpretation. Most studies, however, are preoccupied with the gender of the name, assuming that Junia's apostolic status is not in doubt. This article addresses the latter issue. The collocation of επισημος with its adjuncts shows that, as a rule, επισημος with a genitive personal adjunct indicates an inclusive comparison (‘outstanding among’), while επισημος with (εν plus) the personal dative indicates an elative notion without the implication of inclusion (‘well known to’). This study concludes that Junia was well known to the apostles rather than outstanding among them.